2016
DOI: 10.1155/2016/3456510
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese Herbal Decoction, Huoxue Qingyi Decoction, Promotes Rehabilitation of Patients with Severe Acute Pancreatitis: A Retrospective Study

Abstract: Severe acute pancreatitis (SAP) still remains an important surgical problem with high morbidity and mortality. The utilization of Traditional Chinese Medicine shows good prospects in therapy of SAP since it has advantages of more extensive pharmacological effects and fewer adverse effects. In this retrospective study, 38 patients received standardized treatment (control group) and 37 patients received Chinese herbal decoction, Huoxue Qingyi Decoction (HQD group), in addition to standard treatment for SAP. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Apart from these, other Chinese herbal formulas including Liuhedan (Peng et al, 2013), Huoxueingyidecoction (Ji et al, 2016), Tongxiahuayu decoction (Fang et al, 2007), Yihuoqingyi decoction (Chen et al, 2011), Chaihusihuang decoction (Wang H. et al, 2009), Dachaihu decoction (Cheng et al, 2008), and Qingyichengqi decoction (Zhang et al, 2014) are also effective treatments for AP.…”
Section: Chinese Herbal Formulasmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these, other Chinese herbal formulas including Liuhedan (Peng et al, 2013), Huoxueingyidecoction (Ji et al, 2016), Tongxiahuayu decoction (Fang et al, 2007), Yihuoqingyi decoction (Chen et al, 2011), Chaihusihuang decoction (Wang H. et al, 2009), Dachaihu decoction (Cheng et al, 2008), and Qingyichengqi decoction (Zhang et al, 2014) are also effective treatments for AP.…”
Section: Chinese Herbal Formulasmentioning
confidence: 99%
“…Moreover, our previous study found that Yinchenhao decoction (YCHD), known as an anti-inflammatory and choleretic agent, may also be a potential therapy for AP through pro-apoptosis, anti-inflammation, anti-oxidation, and regulation of lipid metabolism partially via regulating the NF-kB/PPARγ signaling pathway ( Xiang et al, 2016 ). Apart from these, other Chinese herbal formulas including Liuhedan ( Peng et al, 2013 ), Huoxueingyidecoction ( Ji et al, 2016 ), Tongxiahuayu decoction ( Fang et al, 2007 ), Yihuoqingyi decoction ( Chen et al, 2011 ), Chaihusihuang decoction ( Wang H. et al, 2009 ), Dachaihu decoction ( Cheng et al, 2008 ), and Qingyichengqi decoction ( Zhang et al, 2014 ) are also effective treatments for AP.…”
Section: Chinese Herbal Formulasmentioning
confidence: 99%
“…The famous TCM Qingyi decoction has been shown to have clinical benefits in the treatment of SAP[ 5 , 7 ]. However, the challenges associated with its oral administration, complex components, and difficult-to-control quality limit its application and formulation.…”
Section: Discussionmentioning
confidence: 99%
“…The most famous formula for the treatment of SAP is Qingyi decoction, which is composed of rheum, Chinese thorowax root, white peony root, baikal skullcap root, coptis chinensis, and other herbs and has been advocated for more than one hundred years in China[ 5 , 6 ]. Qingyi decoction has exhibited good therapeutic effects in individuals with SAP in many clinical and pre-clinical studies[ 7 - 9 ]. However, use of this decoction is limited because patients are not allowed access to food and water in the acute stage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the formula did not induce any adverse effects such as liver injury. Therefore, huoxueqingyi decoction provides an effective, safe and economic therapeutic option[ 31 ].…”
Section: Tcm Formulasmentioning
confidence: 99%